Multilingualism: Its open and hidden agendas - Komorowska, Hanna (Studies in Second Language Learning and Teaching, 2013)
The author analyses tendencies presented in recently launched EU reports claiming that newly published data reveal a need to rethink approaches to individual and social multilingualism. In the first part of the article approaches to individual as well as to societal multilingualism are discussed from a historical perspective. In the second part meanings ascribed to the promotion of multilingualism are analysed from the language perspective together with the use made of them in the field of social and political activity. Promoting multilingualism is then looked at from the perspectives of the learner and the teacher. Implications are finally sought for teaching, learning and assessment in language education.